UPAYA MENJAGA NETRALITAS APARATUR SIPIL NEGARA DALAM PEMILIHAN UMUM DAN PEMILIHAN KEPALA DAERAH SERENTAK 2024 - R. Sigit Widiarto (Sekolah Tinggi Pariwisata Mataram, 2022)
In 2024, general elections and regional head elections will be held in Indonesia. Given the large number of state civil servants, it can be expected that the participants in the general election will compete for support from the state civil apparatus, even though various regulations regulate the neutrality of the state civil apparatus. This study wants to explain the efforts to maintain the neutrality of the state civil apparatus in the general election and regional head elections in 2024. This research is a normative legal research and uses secondary data consisting of primary legal materials and secondary legal materials. The data were analyzed by interpreting, giving judgments and opinions and then drawing conclusions. The results of this study show that efforts to maintain the neutrality of the state civil apparatus in the general election and regional head elections in 2024 can be carried out through the synergy of several institutions namely the State Civil Apparatus Commission, Bureaucratic Leaders, Regional Inspectorate, General Election Commission, Election Supervisory Body so that it can run smoothly. optimal. Coordination between these institutions should be carried out from the beginning of the stage of holding the general election to strengthen awareness of the importance of maintaining the neutrality of the state civil apparatus and develop new methods that prioritize preventive measures so that violations of the provisions on neutrality of the state civil apparatus do not occur.